THE IMPACT OF THE PHYSICAL ENVIRONMENT, PRODUCT PRICE, AND PRODUCT QUALITY ON CONSUMER IMPRESSIONS AT SKAPAT COFFEE - Apriliani Rafita Ningsih; Dhany Efita Sari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The purpose of this study is to examine the relationship between the physical environment, product price and product quality to consumer impressions. Quantitative research method with commercial causal design. The sample used amounted to 85 customers of Skapat Coffee House, Boyolali. The sample was carried out with a saturated sample, with a data collection method by spreading questionnaires. The data were processed with SPSS using multiple linear regression analysis methods. The results of the study revealed that the physical environment, price and product quality have an influence on consumer impressions at Skapat Coffee House. Thus, a well-managed physical environment, pricing and good product quality will be able to influence the impression of a consumer. Consumers that must be paid attention to by coffee lovers.